Maximum opening of the mouth by mouth prop during dental procedures increases the risk of upper airway constriction - Hiroshi Ito; Hiroyoshi Kawaai; Shinya Yamazaki; et al (Dove Medical Press, 2010)
Hiroshi Ito1, Hiroyoshi Kawaai1, Shinya Yamazaki1, Yosuke Suzuki21Division of Systemic Management, Department of Oral Function, 2Division of Radiology and Diagnosis, Department of Medical Sciences, Ohu University, Post Graduate School of Dentistry, Koriyama City, Fukushima Prefecture, JapanAbstract: From a retrospective evaluation of data on accidents and deaths during dental procedures, it has been shown that several patients who refused dental treatment died of asphyxia during dental procedures. We speculated that forcible maximum opening of the mouth by using a mouth prop triggers this asphyxia by affecting the upper airway. Therefore, we assessed the morphological changes of the upper airway following maximal opening of the mouth. In 13 healthy adult volunteers, the sagittal diameter of the upper airway on lateral cephalogram was measured between the two conditions; closed mouth and maximally open mouth. The dyspnea in each state was evaluated by a visual analog scale. In one subject, a computed tomograph (CT) was taken to assess the three-dimensional changes in the upper airway. A significant difference was detected in the mean sagittal diameter of the upper airway following use of the prop (closed mouth: 18.5 ± 3.8 mm, maximally open mouth: 10.4 ± 3.0 mm). All subjects indicated upper airway constriction and significant dyspnea when their mouth was maximally open. Although a CT scan indicated upper airway constriction when the mouth was maximally open, muscular compensation was admitted. Our results further indicate that the maximal opening of the mouth narrows the upper airway diameter and leads to dyspnea. The use of a prop for the patient who has communication problems or poor neuromuscular function can lead to asphyxia. When the prop is used for patient refusal in dentistry, the respiratory condition should be monitored strictly, and it should be kept in mind that the “sniffing position” is effective for avoiding upper airway constriction. Practitioners should therefore consider applying not only systematic desensitization, but also general anesthesia to the patient who refuses treatment, because the safety of general anesthesia has advanced, and general anesthesia may be safer than the use of a prop and restraints.Keywords: mouth prop, dental procedure, upper airway constriction, asphyxia, maximum opening of the mouth, risk management